Implementasi Sistem Pemidanaan Dua Jalur (Double Track System) bagi Pelaku Penyalahguna Narkotika sebagai Upaya untuk Mengurangi Overcrowding di dalam Lembaga Pemasyarakatan - Fransilirus Nong Richi (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2023)
The main discussion of this research is related to the application of punishment for narcotics abusers which is considered inappropriate. The main problem in this research is related to the application of the double track system as an effort to reduce overcrowding in correctional institutions, as well as analysing the considerations of the panel of judges who tend to ignore the double track system and prefer to apply prison sanctions, such as in the Tanjung Balai Karimun District Court Decision Number: 119/Pid.Sus/2021/PN Tbk and Metro District Court Decision Number: 70/Pid.Sus/2021/PN Met. This research method is a form of normative juridical research that is sourced from secondary data and supported by primary data. The results of this study conclude that placing narcotics abusers in correctional institutions actually exacerbates overcrowding, which has currently reached 109% (one hundred and nine percent). It is then necessary to build a paradigm of stopping criminalisation or by decriminalising narcotics abusers. The concept of decriminalisation is to implement a double track system of punishment, as a form of sanction other than criminal sanctions, such as Portugal and Thailand, which have implemented this system of punishment and proven successful in reducing overcrowding.